Efektifitas Model Inquiry Social Complexcity (ISC) untuk Meningkatkan Keterampilan Berpikir Kritis di Sekolah Dasar - Ade Bagus Putri; Ryzal Perdana; Muhammad Kaulan Karima (LPPM Universitas 17 Agustus 1945 Semarang, 2025)
Abstract. This study aims to determine how effective the Inquiry Social Complexity (ISC) model is in increasing critical thinking in elementary schools. The Inquiry Social Complexity (ISC) learning model is a way of learning that focuses on the use of critical thinking and social complexity to identify and resolve dilemmas. Critical intelligence means cognitive skills that demonstrate a high level of thinking skills, involving analysis, drawing conclusions, and assessing the problem-solving process, which is one of the important competencies in the 21st century. This study uses a quantitative approach using the Pratung Pre-Experimental design. The design applied is the One Group Pretest-Posttest Design. After the treatment was given, the average homogeneous value obtained was 78.11, while the t-test results gave a sig value (2-tailed) of 0.00 with a significance level of 5%. These results indicate that sig (2-tailed) is less than 0.05, so the alternative hypothesis (Ha) is accepted and the null hypothesis (H0) is rejected. This means that there is a significant disparity between the pretest and posttest. The conclusion of this study is an example of Inquiry Social Complexity (ISC) learning that has effectiveness in improving critical thinking skills of students in PPKn subjects at Elementary School 1, class V, Natar District. In addition, the analysis with the n-gain test produced an n-gain of 0.511 which is classified as moderate, which strengthens the acceptance of the other method hypothesis (Hα). This confirms that there has been a significant disparity between the pretest and posttest, regarding the effectiveness of the Inquiry Social Complexity (ISC) learning model on students' thinking skills in PPKn subjects at SDN 1, class V, Natar District.